A mediação cultural na Bienal de Curitiba de 2015 Luz do Mundo - Adayme, Shana Lima (2019)
I worked as the educational coordinator in the Biennial of Curitiba Light of the World from October 2015 to February 2016. This opportunity allowed me to experience the cultural mediation in the spaces occupied by the Biennale. From this experience, I presented a report on the Mediators training, and an analysis of the cultural mediations that took place in the exhibition. As a methodological approach, I conducted interviews with a sample of mediators using photographic records of the event and the testimonies present in the Oscar Niemeyer Museum's Notebook of Mediators. The statements and reports are intended to bring the voices of the mediators to dialogue with authors of CTS, Cultural Studies and Art Education. Therefore, the research sought to understand how the Mediators Training Course and the mediators' educational practices of the 2015 Curitiba Biennale were related.